2017
DOI: 10.1515/prolas-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Body Composition and Energy Intake of Young Female Ballet Dancers and Ordinary School Girls

Abstract: Communicated by Andris Ferdats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In young athletes, the lowest protein intake was 11.9±0.4%TEI 32 and the highest protein intake was 17.5±1.0%TEI 16 . In young non-athletes, the lowest was 12.5±0.5%TEI 32 and the highest was 20.7±5.1%TEI 33 ( Table 1 ). Protein intake was not significantly different between athletes and non-athletes (MD=–0.53%TEI, 95% CI [–1.35; 0.29], p =0.19).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In young athletes, the lowest protein intake was 11.9±0.4%TEI 32 and the highest protein intake was 17.5±1.0%TEI 16 . In young non-athletes, the lowest was 12.5±0.5%TEI 32 and the highest was 20.7±5.1%TEI 33 ( Table 1 ). Protein intake was not significantly different between athletes and non-athletes (MD=–0.53%TEI, 95% CI [–1.35; 0.29], p =0.19).…”
Section: Resultsmentioning
confidence: 98%
“…However, the present meta-analysis revealed that, despite additional requirements related to sport practice, young athletes did not increase their protein intake compared to non-athletes (in %TEI). Lack of difference in protein intake between athletes and non-athletes could be partly explained by a somewhat high protein intake of non-athletes as suggested by the negative difference (-0.53 %TEI, p = 0.19) and some quite high values reported by Kalnina et al [33] (20.7 %TEI) and Moen et al [34] (17 %TEI). In France, the ESTEBAN survey (2014-2016) reported that 37 % of boys and 22 % of girls were considered to be high consumers of meat, fish and eggs, the main foods that provide protein [42].…”
Section: Differences Between Athletes and Non-athletes And Moderatorsmentioning
confidence: 88%
See 1 more Smart Citation